2021
DOI: 10.34172/bi.2021.22167
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells therapy alone does not lead to the complete restoration of the skin parameters in diabetic foot patients within a 3-year follow-up period

Abstract: Introduction: Mesenchymal stromal cells (MSCs) administration is an effective option for the treatment of diabetic foot ulcers (DFUs). However, to date, studies assessing long-term outcomes and evaluating skin parameters after cell-based therapy are lacking. We presented the clinical outcomes of 3 patients, treated for DFUs with the bone marrow MSCs 3 years earlier. Methods: Ultrasound examination was used to compare collagen density and epidermal thickness in areas of healed ulcers in comparison with non-affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Thus, loss of vision was a negative reaction to adipose-derived MSC therapy in three patients with age-related macular degeneration ( 63 ). In another study, MSCs therapy alone does not lead to the full-thickness restoration of ulcerated skin after topical administration ( 64 ). The effectiveness of adipose- and bone marrow-derived MSC in the treatment of lateral amyotrophic sclerosis is also controversial.…”
Section: Major Adverse Events After Cell Injection: Thromboembolism A...mentioning
confidence: 99%
“…Thus, loss of vision was a negative reaction to adipose-derived MSC therapy in three patients with age-related macular degeneration ( 63 ). In another study, MSCs therapy alone does not lead to the full-thickness restoration of ulcerated skin after topical administration ( 64 ). The effectiveness of adipose- and bone marrow-derived MSC in the treatment of lateral amyotrophic sclerosis is also controversial.…”
Section: Major Adverse Events After Cell Injection: Thromboembolism A...mentioning
confidence: 99%
“…Furthermore, the long-term outcomes and the effectiveness of MSC-based cell therapies still need to be improved. Maksimova’s and Zhang’s studies showed that topical administration of MSCs is a safe and promising option, but it took effect mainly in the initial wound closure at an early stage [ 39 , 40 ]. Here, we provide a new method to enhance the effectiveness of MSCs and maybe improve the long-term outcomes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, some studies show that there are no strong correlations between the amount of administered cells and the therapeutic effect [ 140 ]. In fact, recently, in vitro cultured cells exerted promising therapeutic results when administered at low doses of less than 40 × 10 3 cells per 1 cm 2 of a skin wound surface [ 141 ]. Interestingly, in a rat critical-sized bone defect, seeding of β-TCP with minimally manipulated BM-MNCs increased the volume of a newly formed bone, however, seeding of 5 × 10 6 cells led to more pronounced bone formation compared to 1 × 10 7 cells, and the highest mineral bone density was observed in β-TCP seeded with 1 × 10 6 cells [ 140 ].…”
Section: Discussionmentioning
confidence: 99%